LncRNA PTENP1 inhibits cervical cancer progression by suppressing miR-106b - Yingrui Fan; Weiwei Sheng; Yi Meng; Yundi Cao; Rong Li (Artificial Cells, Nanomedicine, and Biotechnology)
LncRNA PTENP1 is a competitive endogenous RNA (ceRNA) involved in decoying miR-106b in multiple diseases. This study investigates the interaction of PTENP1 and miR-106b in cell proliferation, apoptosis and epithelial–mesenchymal transition (EMT) in cervical cancer. The expressions of PTENP1, miR-106b and PTEN were determined in cervical cancer tissues, adjacent normal tissues, cervical cancer cells (HeLa, SiHa, C33A and CasKi) and normal cervical epithelial H8 cells. Up-regulation of PTENP1 and down-regulation of miR-106b were conducted in HeLa and CasKi cells by transfecting cells with corresponding miRNA mimics and inhibitors. Bioinformatics analysis, luciferase reporter assay and RNA-pull down assay were performed to verify the association of miR-106b, PTEN, and PTENP1. Cell growth and cell apoptosis were determined by CCK-8 and flow cytometry analysis. It was found that the expressions of PTENP1 and PTEN were up-regulated and that of miR-106b were down-regulated in cervical cancer tissues and cells. PTENP1 localized in cytoplasm and competitively bound to miR-106b. Up-regulation of PTENP1 and down-regulation of miR-106b contributed to increased expressions of PTEN and E-cadherin. Decreased expression of miR-106b, ZEB1, Snail and Vimentin, resulted in inhibiting cell proliferation and promoting cell apoptosis. Over-expression of PTENP1 and miR-106b accelerated cell proliferation and slowed down cell apoptosis. miR-106b inhibited the expression of PTEN. Our results suggest that LncRNA PTENP1 inhibits cervical cancer progression by competitively binding to miR-106b, leading to promote PTEN expression, inhibit cell proliferation and EMT and induce cell apoptosis in cervical cancer cells